Trastuzumab Provides a Comparable Prognosis in Patients With HER2-Positive Breast Cancer to Those With HER2-Negative Breast Cancer: Post Hoc Analyses of a Randomized Controlled Trial of Post-Mastectomy Hypofractionated Radiotherapy - Sun, Guang-Yi; Jing, Hao; Wang, Shu-Lian; Song, Yong-Wen; Jin, Jing; Fang, Hui; Liu, Yue-Ping; Ren, Hua; Tang, Yu; Zhao, Xu-Ran; Song, Yu-Chun; Chen, Si-Ye; et al. (Frontiers in Oncology, 2021)
Background and Purpose We investigated the locoregional effect of trastuzumab, and determined whether patients with human epidermal growth factor receptor (HER)2-positive breast cancer (BC) treated with trastuzumab could achieve comparable efficacy to that of patients with HER2-negative BC. Materials and Methods This was post hoc analyses of data of 793 BC patients from a randomized controlled trial comparing post-mastectomy hypofractionated radiotherapy with conventional fractionated radiotherapy. Survival rates were analyzed by the Kaplan–Meier method and compared by the log-rank test. Results Patients were classified into three groups: HER2-negative (HER2−; n = 547), HER2-positve with trastuzumab (HER2+ + T; n = 136), and HER2-positive without trastuzumab (HER2+ − T; n = 110). The HER2+ + T group had significantly lower locoregional recurrence (LRR, 6.0% vs. 13.9%), distant metastasis (DM, 17.4% vs. 33.8%) and higher disease-free survival (DFS, 81.2% vs. 61.9%) at 5 years than that of the HER2+ − T group (P <.05). The HER2− group had significantly lower LRR (6.8% vs. 13.9%), DM (22.4% vs. 33.8%) and higher DFS (76.1% vs. 61.9%) at 5 years than that of the HER2+ − T group (P <.05). The difference in LRR, DM and DFS at 5 years was not significant between the HER2+ + T group and HER2− group (P >.05). Different annual LRR patterns was found among groups according to HR status. Conclusion Trastuzumab reduces LRR in patients with locally advanced HER2-positive BC who have received post-mastectomy radiotherapy. It provides comparable DFS to that with patients with HER2-negative BC.